Pertanggungjawaban Pidana Anak Pelaku Penyalahguna Narkotika Perspektif Hukum Pidana Islam - Yesy Yuvita; Evi Ariyani (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
Decision number 03/Pid.sus-Anak/2018/PN.Skt regarding child offenders who abuse narcotics even though the child has been legally and convincingly proven guilty in article 127 paragraph 1 letter a of law number 35 of 2009, but the child is only given a lenient criminal sentence. The research was conducted to examine the criminal liability of children as drug users. The research method used is qualitative research with normative research. The data analysis techniques used is content analyis. The result of this research explain that the criminal responsibility of children who abuse drugs in verdict number 03/Pid.sus-Anak/2018/PN.Skt is because children have fulfilled the theory of criminal responsibility and based on law number 11 of 2012 children can be held accountable for their actions, the sentence given is to undergo treatment at the SINAI Sukoharjo Mental and Drug Rehabilitation Foundation for 6 (six) months, the decision is also based on the judge’s consideration. Meanwhile, in Islamic criminal law, children as perpetrators of criminal acts will not be subject to punishment in the form of hudud, qishas/diyat, or ta’zir. Children will only be subject to ta’dibi which is coaching that provides lessons but does not affect their psycholog.